The Efficacy of a Calamansi-Containing Energy Drink on Running Performance and Recovery in NCAA Division I Middle-Distance Runners: A Preliminary Study - Abdullah B. Alansare (MDPI AG, 2021)
This study examined the effects of a non-caffeinated energy drink (ED) that contained calamansi juice, glucose, and taurine on 3-km running performance and recovery. Eleven NCAA Division I middle-distance runners (20.8 ± 1.5 years old) were randomly assigned to consume either the ED or a placebo drink 60 min before 3-km running on a 400-m official track. Performance time and speed were recorded every 500-m interval. Recovery blood lactate concentration (BLC), systolic (SBP), diastolic blood pressure (DBP), and heart rate (HR) were measured at baseline, 60-min after ingesting the drinks, and post-running measurements were performed at 1-min, 5-min, and 10-min. Repeated analysis of variance and paired t-test were applied to examine the effects of time, trials, and their interaction on performance and recovery. Statistical significance was set a priori at p < 0.05. No significant difference was observed in performance time and speed between trials (p < 0.05). No interaction effect was found on performance time, speed, recovery BLC, DBP, and HR (p < 0.05). However, an interaction effect for trial by time was observed on SBP (p = 0.01). Recovery SBP continues to decrease from 5-min to 10-min in the ED trial (∆ = −13.9 mmHg) and slightly increased in the placebo trial (∆ = 1.1 mmHg). This study suggests that acute consumption of a calamansi-containing ED can positively impact the SBP recovery but not running performance. Further studies are needed to examine the acute and chronic effects of this ED on exercise performance and recovery among different populations.